X-ray spectroscopy unfolding the effects of glyphosate on soybean (Glycine max L.) manganese foliar uptake - Machado, Bianca de Almeida (2020)
The spraying of tank mixtures with manganese (Mn) and glyphosate allows the nutrition of soybean crops resistant to glyphosate, while controlling weeds. However, complexation reactions can occur between these species, which has the potential to significantly decrease the efficiency of this operation. Thus, this study aimed to investigate the chemical reactions and the absorption of Mn by soybean supplied as MnSO4, MnCO3, Mn-ethylenediamino-tetraacetic (Mn-EDTA), Mn-phosphite and Mn-glycine. In tank mixtures, approximately 30% of the Mn supplied via MnSO4 and Mn-glycine precipitated together with glyphosate molecules, in ca. 2:1 Mn:glyphosate molar ratio. X-ray absorption spectra (XAS) of the precipitates indicated that they presented the same chemical environment regardless of the employed source, this technique did not show evidence of soluble complexes. The use of Mn-EDTA, as well as maintaining the pH of the mixture below 2.5 prevents precipitation, while pH above 7 resulted in MnO(OH). MnSO4, MnCO3, Mn-EDTA and Mn-phosphite solutions/dispersions, with and without glyphosate, applied to soybean leaflets damaged the leaf cuticle, regardless of the glyphosate mixture. Except for MnCO3, all sources increased the Mn content in the treated leaf petioles. The glyphosate mixture reduced the absorption and transport of Mn when supplied via MnSO4 and Mn-phosphite, but XAS analysis showed no evidence of complexation of Mn by glyphosate inside the plants. The absorbed manganese is transported in a similar chemical environment when supplied as MnSO4 and Mn-phosphite, but Mn-EDTA was found in its pristine form in the treated petioles. The foliar absorption of droplets of MnSO4 and Mn-EDTA, with and without glyphosate, was monitored for 72 hours, following a sigmoid tendency of absorption. The glyphosate mixture decreased the leaf absorption of MnSO4 due to the precipitation of complexes on the leaf surface, but no effect on the absorption of Mn-EDTA was observed. The absorption of MnCO3 followed linear behavior, being absorbed very slowly. The application of glyphosate in conjunction with MnSO4 increased the activity of the superoxide dismutase enzyme (SOD), probably due to the unavailability of Mn for leaf absorption. The results presented in this study show that the efficiency of foliar fertilization with Mn is reduced due to interactions that occur in solutions where free Mn2+ ions are available for complexation at pH above 2.5. No evidence of intracellular complexation was found. In this sense, the employment of chelated sources, such as Mn-EDTA, is an alternative to enable the application of tank mixtures in glyphosate-resistant soybean crops without losing the efficiency of the operation